Housing Development Account (‘HDA’) for Private Housing Developers in Peninsular Malaysia: Law and Legal Issues - Md Dahlan, Nuarrual Hilal (Lexisnexis Malaysia Sdn. Bhd, 2019)
In Peninsular Malaysia, it is a mandatory requirement that all housing developers who carry out housing development must open a Housing Development Account (‘HDA’). The housing developers are only allowed to use the funds subject to the conditions of the Housing Development (Control and Licensing) Act 1966 (‘Act 118’). Thus, the purchasers’ money can be protected. Nonetheless, despite this law, some practices have caused losses to purchasers. This paper highlights this issue through two case studies of housing projects in Peninsular Malaysia. The author used a composite of a qualitative case study and legal research methodologies to explain and analyse the issues in this paper. The author finds that despite there being a law governing the HDA, there are still dishonest methods used by irresponsible housing developers that have caused irreparable damage to purchasers. At the end of this paper, the author suggests ways to overcome the problems.